EFEKTIVITAS METODE COOPERATIVE CONCEPT SENTENCE TERHADAP KEMAMPUAN MENULIS KELAS V SDN PENGGUNG UTARA KOTA CIREBON - Setianingsih, Indah; Kusuma, Dewi; Nabillah, Rokhmatun (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2026)
Abstract Writing skills are one of the essential basic competencies that elementary school students must master, particularly in the Indonesian language subject. However, field observations indicate that many fifth-grade students at SDN Penggung Utara, Cirebon City, still experience difficulties in constructing sentences, using punctuation, and developing ideas coherently and logically. The purpose of this study is to describe the process of implementing the Cooperative Concept Sentence learning approach to improve the writing skills of fifth-grade elementary school students and to analyze the effectiveness of this approach in enhancing their writing abilities. This study employs a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The research subjects consisted of 26 fifth-grade students who received treatment in the form of learning activities using the Cooperative Concept Sentence method. Data were collected through speech text writing tests (pretest and posttest) and observations of students’ learning activities. The data were analyzed using the Paired Sample T-Test and N-Gain calculation. The results show that the Cooperative Concept Sentence method is effective in improving students’ writing skills. The average pretest score of 57.04 increased to 85.08 in the posttest, with an N-Gain value of 0.635 or 63.5%, which falls into the medium category based on Hake’s (1999) criteria. The Paired Sample T-Test indicates a significance value of 0.001 < 0.05, demonstrating a significant difference between students’ performance before and after the treatment. Improvements were observed across all writing indicators, including sentence structure, vocabulary, paragraph coherence, idea development, as well as punctuation and spelling accuracy. Thus, the implementation of the Cooperative Concept Sentence method is proven to be effective in enhancing the writing skills of elementary school students. Keywords : Cooperative Concept Sentence, writing skills, Indonesian language learning, SDN Penggung Utara.